2009
DOI: 10.1055/s-0029-1237704
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Follow-up of Patients with Adrenal Incidentalomas- A Single Center Experience and Review of the Literature

Abstract: AIs present usually as benign, non-secretory lesions. Criteria for surgical intervention were met at initial assessment for the majority of AIs. Size alterations during follow-up are uncommon and functional evolution is rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…Even in patients in whom a significantly increasing mass (≥1 cm/year) was observed, the final pathological diagnosis was confirmed as benign after surgical resection. The majority of previous cohort studies, which comprised sample sizes of 24-187 patients and had median follow-up periods of 1.8-7.5 years, similarly revealed no malignant transformation in typical benign nonfunctional AIs (20,21,22,23,24,25,26). One systematic review including data from 1081 patients reported an incidence of adrenal malignancy of 0.2% (only 1 case) (4).…”
Section: :6 481 Clinical Studymentioning
confidence: 95%
“…Even in patients in whom a significantly increasing mass (≥1 cm/year) was observed, the final pathological diagnosis was confirmed as benign after surgical resection. The majority of previous cohort studies, which comprised sample sizes of 24-187 patients and had median follow-up periods of 1.8-7.5 years, similarly revealed no malignant transformation in typical benign nonfunctional AIs (20,21,22,23,24,25,26). One systematic review including data from 1081 patients reported an incidence of adrenal malignancy of 0.2% (only 1 case) (4).…”
Section: :6 481 Clinical Studymentioning
confidence: 95%
“…13,61 Moreover, the so-called "clear cell variant" (lipid degeneration) of pheochromocytoma may show significant morphologic overlap with metastatic CC-RCC. 13,61 Moreover, the so-called "clear cell variant" (lipid degeneration) of pheochromocytoma may show significant morphologic overlap with metastatic CC-RCC.…”
Section: Pheochromocytomamentioning
confidence: 99%
“…By contrast, the 2016 ESE guidelines recommend that adrenal masses <40 mm with clear benign features do not require follow‐up imaging, irrespective of their history of extra‐adrenal malignancy . The majority of previous cohort studies, which comprised sample sizes of 24‐637 patients and had median follow‐up periods of 1.8‐7.5 years, similarly revealed no malignant transformation in typical benign nonfunctional AIs . One systematic review including data from 1081 patients reported an incidence of adrenal malignancy of 0.2% …”
Section: Discussionmentioning
confidence: 99%
“…12 The majority of previous cohort studies, which comprised sample sizes of 24-637 patients and had median follow-up periods of 1.8-7.5 years, similarly revealed no malignant transformation in typical benign nonfunctional AIs. 20,21,24,27,[30][31][32][33][34] One systematic review including data from 1081 patients reported an incidence of adrenal malignancy of 0.2%. 35 In the present study, most nonfunctional adrenal masses remained stable in size during the long-term follow-up period, and no malignancy was diagnosed.…”
Section: Discussionmentioning
confidence: 99%